2022
DOI: 10.1155/2022/2923941
|View full text |Cite
|
Sign up to set email alerts
|

Human Gut Microbes Associated with Systolic Blood Pressure

Abstract: Emerging studies have revealed a strong link between the gut microbiome and several human diseases. Since human gut microbiome mirrors variations in lifestyle and environment, whether associations between disease conditions and gut microbiome are consistent across populations—particularly in communities practicing traditional subsistence strategies whose microbiomes differ markedly from industrialists—remains unknown. Cardiovascular diseases are the leading cause of mortality in India affecting 55 million peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Our data showed that F/B ratio in hypertensive patients was higher than that of non-hypertensives. Yang et al (2015) and Joishy et al (2022) have also reported that the (F/B) ratio was found increased in hypertensive patients. Given an imbalanced F/B ratio in hypertensive patient, we know that there is the alteration of gut microbiota composition towards dysbiosis correlated with this particular cardiovascular disease.…”
Section: Discussionmentioning
confidence: 84%
“…Our data showed that F/B ratio in hypertensive patients was higher than that of non-hypertensives. Yang et al (2015) and Joishy et al (2022) have also reported that the (F/B) ratio was found increased in hypertensive patients. Given an imbalanced F/B ratio in hypertensive patient, we know that there is the alteration of gut microbiota composition towards dysbiosis correlated with this particular cardiovascular disease.…”
Section: Discussionmentioning
confidence: 84%
“…This direct relationship between F/B ratio and BP has also been documented in various mouse models (Marques et al, 2017 ; Toral et al, 2018 ). Similarly, human studies (Mushtaq et al, 2019 ; Silveira-Nunes et al, 2020 ; Joishy et al, 2022 ) also support a direct relationship between F/B ratio and BP. In contrast, cold-induced HTN (Wang et al, 2022 ) is one of the rare contexts wherein F/B ratio was not altered significantly.…”
Section: Gut Microbiota and Htnmentioning
confidence: 82%
“…Supporting this notion, studies have shown that F. prausnitzii is significantly abundant in normotensive compared to hypertensive humans, demonstrating strong correlation of this specific microbe with BP (Yan et al, 2017;Calderón-Pérez et al, 2020). However, in contradiction, Faecalibacterium was more enriched in individuals with high BP (Joishy et al, 2022). Therefore, there is a need to directly examine the potential of F. prausnitzii in rigorous animal model studies.…”
Section: Gut Microbiota As Therapeutic Targetsmentioning
confidence: 99%
“…Interestingly, the Coprococcus genus has been linked to normal blood pressure [151]. Conversely, a study by found that hypertensive patients had a higher abundance of species from the Roseburia genus [152], whereas, for the Faecalibacterium genus, the results are conflicting; some studies have associated a higher abundance of the genus with hypertension, while others have correlated a lower relative abundance with hypertension [152][153][154].…”
Section: Potential Harmful Effects Of Meddiet Componentsmentioning
confidence: 99%